(untitled) (Research, Society and Development, 2023)
This narrative review of the literature aims to present the changes in the epidemiological profile of oropharyngeal cancer, with the aim of understanding its current perspectives, with emphasis on the association with HPV infection and the role of the dentist in this condition, through the currently available measures. To this end, an integration was carried out between reference books, information from competent bodies and a search for studies from the last five years in the databases: PUBMED, SciELO and LILACS, although only the PUBMED database provided studies for the research model used. Of the 107 studies identified, 22 were included in the work for discussion and, despite the heterogeneity of information, there was agreement on the fact of the growing and current association between HPV and oropharyngeal cancer. However, there are still many gaps to be filled, especially regarding screening methods, monitoring of high-risk cases, early detection and diagnosis. In this sense, awareness, health education for professionals and patients and vaccination against HPV are the measures currently discussed as potentially effective.